Targeted m(6)A Reader Proteins To Study Epitranscriptomic Regulation of Single RNAs - Rauch, Simone (J Am Chem Soc, 2018)
Post-transcriptional gene expression regulation of RNA has emerged as a key factor that controls mammalian protein production. RNA trafficking, translation efficiency, and stability are all controlled at the transcript level. For example, in addition to the commonly known processing steps of capping, splicing, and polyadenylation, RNA can be chemically modified. In eukaryotes, N(6)-methyladenosine (m (6)A) is the most prevalent mRNA modification. While the writers, erasers, and readers for m(6)A are rapidly being uncovered and studied at the whole-cell level, their competitive interplay to regulate methylated RNA transcripts has yet to be elucidated. To address this limitation, we report the development of programmable dPspCas13b-m(6)A reader proteins to investigate the regulatory effects of specific readers on single transcripts in live cells. We fused the two most well-characterized m(6)A reader proteins, YTHDF1 and YTHDF2, to a catalytically inactive PspCas13b protein, which can target the reader to a specific RNA of interest using guide RNA (gRNA) complementarity. We then demonstrate that the fused reader proteins each retain their reported functional role on a reporter construct: YTHDF2 induces degradation and YTHDF1 enhances translation. Finally, we show that the system can target endogenous mRNA transcripts within cells, using YTHDF2 as an exemplar, where we found tethering with YTHDF2 leads to decay of the target transcript. The development of dCas13b-based tools to study the regulation of endogenous RNAs will dramatically enhance our understanding of how RNA regulation occurs at the single RNA level. Additionally, our new tools, which permit transcript-specific mediated decay or enhanced protein production, will find utility in synthetic biology applications aimed at controlling genetic information flow at the RNA level.